1997
DOI: 10.1359/jbmr.1997.12.6.889
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Effects of Glucocorticoids on Collagen Synthesis in Fetal Rat Calvariae by Insulin-like Growth Factor Binding Protein-2

Abstract: To test the hypothesis that insulin-like growth factors (IGFs) play a role in the response of bone to glucocorticoids, we determined the effects of cortisol on the incorporation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 61 publications
4
20
1
Order By: Relevance
“…In contrast to our findings, several previous studies (40)(41)(42)(43) indicate that IGFBP-2 can inhibit IGF action. There are, however, important differences between these studies and our in vivo and in vitro findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, several previous studies (40)(41)(42)(43) indicate that IGFBP-2 can inhibit IGF action. There are, however, important differences between these studies and our in vivo and in vitro findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In this context, we found that C/EBP8 and C/EBPI3 were both induced by transient exposure to low doses of glucocorticoid, and in so doing, increased new IGF-I gene expression in response to agents that generate cAMP In contrast, continuous treatment with highdose glucocorticoid directly suppressed IGF-I mRNA expression. The latter result appears to occur at a point downstream of new C/EBP synthesis, through a mechanism that blocks or perhaps supersedes the stimulatory effect of cAMP on C/EBP activity (McCarthy et al, 1990a(McCarthy et al, , 2000Kream et al, 1997). These findings thus suggest that IGF-I, and perhaps other target genes for C/EBPs, may partly account for permissive effects on skeletal tissue integrity that are related to normal physiological variations in serum glucocorticoid (Fig.…”
Section: (I) the Situationsmentioning
confidence: 82%
“…Experiments using organ cultures of fetal or neonatal bone have shown that exposure to glucocorticoids increases collagen synthesis and alkaline phosphatase activityparameters of osteoblast differentiation -after 24 h of culture, but decreases these parameters after 96 h (Dietrich et al 1979, Canalis 1983, Kream et al 1997. In addition, both stimulation and inhibition of cell proliferation by glucocorticoids have been reported in these organ cultures (Tenenbaum & Heersche 1985, McCulloch & Tenenbaum 1986, Kream et al 1997. In isolated osteoblast-like cell populations, glucocorticoids decrease cell proliferation but increase alkaline phosphatase activity (Chen et al 1977, Wong et al 1990, Cheng et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…They appear to depend upon whether physiological or pharmacological concentrations of the hormone are used, on the time and duration of exposure to the drug, and on the particular system investigated (Bellows et al 1987). Experiments using organ cultures of fetal or neonatal bone have shown that exposure to glucocorticoids increases collagen synthesis and alkaline phosphatase activityparameters of osteoblast differentiation -after 24 h of culture, but decreases these parameters after 96 h (Dietrich et al 1979, Canalis 1983, Kream et al 1997. In addition, both stimulation and inhibition of cell proliferation by glucocorticoids have been reported in these organ cultures (Tenenbaum & Heersche 1985, McCulloch & Tenenbaum 1986, Kream et al 1997.…”
Section: Introductionmentioning
confidence: 99%